Intelligent zebra crossing system - Chevure, Kingdom (Midlands State University, 2020)
The purpose of this study is to design an Intelligent Zebra Crossing system using Arduino. The main objective of the study is to manage and prioritise a smooth flow of the road users without causing any accidents at the zebra crossings, and to enforce the road rule to all those who have been vandalizing it. The system incorporates the concept of passive pedestrian detection to sense the presence of pedestrians and in turn automatically controls the traffic lights. It also makes use of an override pushbutton for in case of the failures faced by the PIR sensor on human detection. A surveillance camera is banded into the system to constantly manage the pedestrian crossing site and provide instant updates on any danger that may occur. Observations have been made to gather information for the study and hence the need to solve problems of the existing system using the proposed system was discovered. Relevant information gathering and electronic designing were incorporated into the designing of the system. Various tools have been used to design the proposed system and these may include Arduino IDE, C++, Arduino Uno microcontroller and sensors. A camera module was also part of the tools that were used in the design. Electric calculations were made on the components so that there will be proper power supply that will not damage the components. Each component was tested during the interfacing of the Arduino board and the components. The proposed intelligent system was tested and the results for all the experiments were recorded, the results confirmed that the system functionality was in agreement with the stated objectives. Finally, the proposed system was implemented hence solving the problems caused by the current system.